CRITERIA FOR A MOSQUE IMAM FROM THE PERSPECTIVE OF THE MOSQUE TAKMIR, HOUSING AND THE VIEWS OF THE SALAF ULAMA - Putra Anu Jaya; Hari Santoso Wibowo; Fathurrahman Fathurrahman (Program Studi Manajemen Dakwah - Fakultas Dakwah dan Ilmu Komunikasi - UIN Syarif Hidayatullah Jakarta, 2026)
The mosque imam plays a strategic role not only as the leader of congregational prayers but also as a spiritual guide, moral role model, and facilitator of the religious and social life of the congregation. This study aims to analyze the criteria of mosque imams from the perspective of residential mosque caretakers (takmir) and compare them with the views of salaf scholars. The research employed a qualitative approach using an exploratory method. Data were collected through in-depth interviews with eight caretakers of residential mosques in Sidoarjo and Gresik. Data analysis was conducted through data reduction, data presentation, conclusion drawing, and verification. The findings indicate that mosque caretakers prioritize several criteria in selecting imams, including proper Qur’anic recitation according to tajwid rules, understanding of prayer jurisprudence, good moral character, discipline, communication skills, and social concern for the congregation. Among these criteria, moral character and exemplary conduct were considered the most important aspects. The study also reveals a strong alignment between the perspectives of mosque caretakers and the views of salaf scholars, who emphasize the principles of al-quwwah (competence) and al-amanah (integrity) in imam selection. This study is expected to serve as a practical reference for mosque management in determining appropriate standards for imams in modern residential communities.